Characterization of antimicrobial activities of Philippine Bee Propolis and sodium nitrite against staphylococcus aureus and salmonella enterica ser. typhimurium in brain-heart infusion broth - Tayamora, Daniel Joshua L.; Gabriel, Alonzo Alulod (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT This study aimed to characterize the individual and combined antimicrobial effects of Philippine bee propolis and nitrite against methicillin-resistant Staphylococcus aureus and Salmonella enterica serovar Typhimurium in brain heart infusion broth (pH 7.2, 37 °C). Increasing concentrations of propolis (0, 3000 and, 6000 ppm) and nitrite (0, 100 and, 200 ppm) were used to assess the individual effects of both additives while a central composite design was used to test the combined effects of propolis and nitrite. Results showed that propolis and nitrite were not able to impart significant individual antimicrobial effect on the growth parameters of the test organisms. However it should be noted that, although not significant, 3000 ppm propolis was able to prolong the lag time of S. aureus to 3.17 h and may prove to be important for products subjected to temperature abuse. Similarly, results showed that all propolis-nitrite combinations did not possess any antimicrobial effect against the test organisms. Several factors may have influenced the results such as the composition of bee propolis, which may be low on antimicrobial constituents, the pH of the growth medium used was relatively high compared to meat systems where nitrite is applied and possible antagonism between nitrite and propolis. Compositional analysis of Philippine bee propolis is strongly recommended to establish a direct correlation between its biological activities and its constituents. Further studies on nitrite replacements in cured meats may also employ different growth conditions closely simulating the pH (5.5-6.2) of meat systems and actual storage conditions (4 C).
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Propolis -- Philippines; Bee products